2000
DOI: 10.1890/1051-0761(2000)010[0890:rtmodt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Regression-Tree Modeling of Desert Tortoise Habitat in the Central Mojave Desert

Abstract: This paper describes an interdisciplinary study of the habitat requirements of threatened desert tortoises (Gopherus agassizii) on eight 225‐ha study plots in a 14 000 ha study area near the southern boundary of the U.S. Army's National Training Center at Fort Irwin in the central Mojave Desert of southern California. The objective of the study was to produce an empirical, statistical, GIS‐based model of desert tortoise habitat use based on a combination of field data and data derived from various spatial data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 22 publications
2
45
0
Order By: Relevance
“…Our study also suggests the importance of shade structures and monitoring along project fencing in the first month post-release to reduce thermal exposure for individual tortoises attempting to home, particularly for short-distance translocations (Hinderle et al, 2015). To further reduce thermal stress, mitigations should ensure suitable habitat for translocated animals, such as adequate shrub cover and loamy soils, that allow tortoises to most easily find shelter and dig burrows (Andersen et al, 2000). Habitat might be enhanced by providing artificial burrows in a 'soft' rather than 'hard' release.…”
Section: Discussionmentioning
confidence: 88%
“…Our study also suggests the importance of shade structures and monitoring along project fencing in the first month post-release to reduce thermal exposure for individual tortoises attempting to home, particularly for short-distance translocations (Hinderle et al, 2015). To further reduce thermal stress, mitigations should ensure suitable habitat for translocated animals, such as adequate shrub cover and loamy soils, that allow tortoises to most easily find shelter and dig burrows (Andersen et al, 2000). Habitat might be enhanced by providing artificial burrows in a 'soft' rather than 'hard' release.…”
Section: Discussionmentioning
confidence: 88%
“…Although other studies have utilized classification and regression tree (CART) models to successfully predict habitat requirements for rare plants (Engler et al 2004) and animals (Anderson et al 2000;Dettmers and Bart 1999), species response to climate change (Iversen andPrasad 1998), coral distributions (De'ath andFabricius 2000), and the distribution of California oak species (Vayssieres et al 2000), our study is the first to utilize these models to predict invasive species habitat. While other studies have shown the utility of CART models for native species management and research, our work demonstrates the same potential for invasive species.…”
Section: Discussionmentioning
confidence: 99%
“…The decision tree algorithm is based on a process called recursive partitioning, which consists of dividing the data into two sets that produce the largest decrease in deviance (i.e. measure of heterogeneity) (Andersen et al, 2000). To create these trees, a randomly elected sample test was selected (n = 1249) (77% of the total cases), while the remaining n = 359 cases were used to test the model.…”
Section: Statistical Analysesmentioning
confidence: 99%